Nasal patency is related to dust exposure in woodworkers. Issue 1 (1st January 2002) - Schlünssen, V; Schaumburg, I; Andersen, N T; Sigsgaard, T; Pedersen, O F
Abstract : Objectives: A cross sectional study of 54 furniture factories and three control factories was conducted to investigate the relation between subjective and objective nasal obstruction and exposure to wood dust. Methods: Acoustic rhinometry was performed on 161 woodworkers and 19 controls. For each person, four measuring rounds were performed: before work, after 4 hours of work, and after 7 hours of work before and after decongestion. Before the first and third measuring round, each person rated the current feeling of nasal obstruction in the left and right nostril separately, using a visual analogue scale. Personal passive dust measurements were performed on 140 woodworkers. Results: The mean (SD) of equivalent inhalable dust was relatively low, 1.17 (0.62) mg/m 3, range 0.17–3.44 mg/m 3 . The exposure was divided into four levels: controls, low exposure, medium exposure, and high exposure. For the two highest concentrations of exposure, a significant increase in congestion—decreased nasal cavity volume and cross sectional areas—was found after 4 and 7 hours of work, compared with before work. Multivariate linear regression analysis showed positive correlations between concentration of dust and change in mucosal swelling. A significant increase in self rated nasal obstruction was found after work compared with before work for the two highest exposure groups. No correlation between objective nasal variables and self rated nasal obstruction was found. Conclusion: Exposure to wood dust was related in a dose dependent manner to acute nasal obstruction measured by acoustic rhinometry and self reported obstruction, but no correlation was found between measured and self reported obstruction.